2018
DOI: 10.3390/jcm7110421
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial Ultrasound under Moderate Sedation versus General Anesthesia

Abstract: Background: Different anesthetic protocols may influence endobronchial ultrasound-guided needle aspiration (EBUS-TBNA) outcomes, patient comfort, and even safety. In this study, two anesthesia techniques were assessed and compared for EBUS-TBNA. Methods: A prospective, multicenter study was carried out. Patients were allocated to Group 1 (general anesthesia with neuromuscular blockade and controlled ventilation) and Group 2 (intravenous sedation). EBUS-TBNA accuracy was the primary outcome. Safety, patient com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…All but one retrospective study reported that diagnostic yield and patient tolerance under deep propofol sedation was equivalent to that under moderate midazolam sedation [ 37 40 ]. Prospective randomised controlled trials comparing the use of propofol for general anaesthesia and midazolam for moderate sedation were also comparable in terms of diagnostic yield, major complications and patient tolerance [ 31 , 41 ]. In the current study, we compared the diagnostic yield and detailed sedative profiles among patients undergoing dexmedetomidine or propofol sedation from the perspective of patients, bronchoscopists and physicians overseeing sedation.…”
Section: Discussionmentioning
confidence: 99%
“…All but one retrospective study reported that diagnostic yield and patient tolerance under deep propofol sedation was equivalent to that under moderate midazolam sedation [ 37 40 ]. Prospective randomised controlled trials comparing the use of propofol for general anaesthesia and midazolam for moderate sedation were also comparable in terms of diagnostic yield, major complications and patient tolerance [ 31 , 41 ]. In the current study, we compared the diagnostic yield and detailed sedative profiles among patients undergoing dexmedetomidine or propofol sedation from the perspective of patients, bronchoscopists and physicians overseeing sedation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 3 ] Anesthetic considerations for the procedure have been an area of much interest and there are plenty of studies making comparisons between different methods. [ 4 5 6 7 8 9 ] EBUS-TBNA under GA as well as with moderate sedation (MS) seems to be safe, [6] effective, and with good diagnostic yield but with comparable disadvantages and advantages, one of them being the higher cost. [10] …”
Section: Discussionmentioning
confidence: 99%
“…In their previous studies, Fernandes et al [6] and Casal et al [8] compared the application of GA and MS in the process of EBUS-TBNA. They pointed out that because some pulmonary physicians did not accept GA, they turned to explore a suitable method for MS of EBUS-TBNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, aspirated specimens are expelled into a container with preservative liquid, and a cytoblocis prepared and stained for subsequent cytological examination. Sedation is performed according to institutional practice [53].…”
Section: Recent Bronchoscopic Techniquesmentioning
confidence: 99%